2022
DOI: 10.1007/s00417-022-05850-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgery-related characteristics, efficacy, safety and surgical team satisfaction of three-dimensional heads-up system versus traditional microscopic equipment for various vitreoretinal diseases

Abstract: Purpose To compare the three-dimensional (3D) heads-up surgery with the traditional microscopic (TM) surgery for various vitreoretinal diseases. Methods A medical record review of patients that underwent 3D heads-up or TM vitreoretinal surgeries was performed from May 2020 to October 2021 in this retrospective case–control study. Main outcome measures included surgery-related characteristics, efficacy, safety, and satisfaction feedback from the surgical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…16 Based on previous research and analysis, 3D surgical video systems have superior visualization capabilities, which can improve the efficiency of membrane peeling in vitrectomy and reduce the incidence of intraoperative complications, especially in complex and long-duration vitreoretinal surgeries. 17 The advantages of 3D surgical video systems in macular surgeries include reduced intraocular illumination and minimized phototoxicity to retinal cells. 18 In addition, the filter function combined with the 3D surgical video system can lower the dye concentration or reduce the dyeing time, thereby reducing possible adverse reactions to the dyes.…”
Section: Discussionmentioning
confidence: 99%
“…16 Based on previous research and analysis, 3D surgical video systems have superior visualization capabilities, which can improve the efficiency of membrane peeling in vitrectomy and reduce the incidence of intraoperative complications, especially in complex and long-duration vitreoretinal surgeries. 17 The advantages of 3D surgical video systems in macular surgeries include reduced intraocular illumination and minimized phototoxicity to retinal cells. 18 In addition, the filter function combined with the 3D surgical video system can lower the dye concentration or reduce the dyeing time, thereby reducing possible adverse reactions to the dyes.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D surgical system has been reported to have multiple advantages including a wider visual field and higher magnification performance compared with the TM system [ 12 , 13 ]. Our previous study further indicated that the 3D heads-up system was associated with a significantly shorter duration of delicate surgical steps, like ILM peeling, than the TM system [ 14 ]. Besides, previous studies also reported the occurrence of iatrogenic circumscribed semicircular rip in the RPE and macular hole caused by the inadvertent injection of the rt-PA [ 31 , 34 , 35 ], which may be avoided using the 3D heads-up system with a higher magnification.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Eckardt et al [8] applied the three-dimensional (3D) heads-up system in complicated posterior segment surgeries, sparking ophthalmologists' interest in using this system to treat vitreoretinal diseases. The 3D heads-up system was reported to have multiple advantages over the TM system, such as higher magnification, a wider visual field, superior stereoscopic sensation, increased depth of field, improved ergonomic design, and enhanced surgical team communication and education [9][10][11][12][13][14]. However, the application of the 3D heads-up system in the treatment of SMH has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, pioneers such as Eckardt, Kita, and others laid the foundation by introducing 3D surgical video systems to vitreoretinal surgery. Additionally, comparisons between the 3D surgical video and traditional microscope-based systems have been conducted, indicating similar surgical durations and postoperative outcomes ( 14 , 16 19 ). Our study contributes to this evolving field by introducing a novel concept, the “stripping efficiency.” This concept demonstrates the distinct advantages of utilizing a 3D surgical video system in proliferative diabetic retinopathy surgeries.…”
Section: Discussionmentioning
confidence: 99%